Padrões de ocupação e grau de especialização das aves florestais : aprofundando o conhecimento ecológico do grupo na região da planície de inundação do alto rio Paraná. - Ramos, Camila Crispim de Oliveira (2014)
Forest fragmentation changes regional and local biodiversity patterns through loss of micro-habitat, isolation of habitat and changes in the dispersion and migration patterns. The relationship of these groups with greater sensitivity to fragmentation and the size of the area are inversely proportional. However the maintenance of large contiguous areas is increasingly rare due to the growing cattle farming. Alternatively the preservation of smaller areas and riparian forests to act as stepping stones or dispersal corridors should be encouraged. Understand the occupation patterns of bird species in fragmented regions and how the affinity of these types of fragments can provide great advances in conservation. Using metacommunities and indicator species approach, we attempted to describe occupation patterns of avifauna in three types of forest fragments in the Upper Paraná River floodplain and assess their quality. These forest fragments correspond to large fragments (> 300 ha), small fragments and riparian forests. It was found that the types of fragments in the region have particular compositions of forest bird species (Pseudo F = 19,51; p < 0,001). However the fragments of the same size class also differ between the two banks of the Paraná River. Within the perspective of metacommunities, the nested distribution was a general pattern. However, interior-preferential species exhibited pattern of distribution Clementsian. Indicator species of riparian fragments belong to a group of species with greater tolerance to the degradation of forest habitat. Only body mass showed a close relationship with the degree of habitat specialization. Through these results we can conclude that the species habitat affinity and limited dispersal between the types of fragments are predominant for maintaining the pattern of bird metacommunity. Each type of forest fragment, by its specific bird composition, plays an essential role in the fragmented landscape. Particular attention should be forest bird species interior-preferential and large species in future conservation actions, because they present highly habitat specialization and therefore have a greater risk of local extinction.